Subjective Well Being Pada Siswa SMP Yang Mengalami Broken Home - Adinigsih, Husna Amalia; , Rini Lestari, S.Psi, M.Si, Psi (2017)
ABSTRACT Subjective well being is the cognitif and emotional evaluation of individual to their life, such as that is understand by layman as the happiness, serenity and the satisfaction of life. Broken home often has the bad impact for a child. This study aims to understaand and describe the condition of subjective well being in junior high school whois broken home. There are six of junior high school students who is broken home. The data collected by using semi structure interview and descriptive observation.The technique of data analysis which is used in this research is interactive techniques consisting of four steps, thatare data collection, data reductive, data disply, and making a conclusion. Based on the result of analysis and discussion can be concluded that subject disposed feels not comfortable when they are at home.The because their parents are busy, and not take care with them and often angry with them. This problem makes the subject furthure from their parents and occuring thesad feeling, dissapointed, bored, lonely and feels so burdened with the circumtances. To get comfortable and happy condition. Then the subject smoking,drinking, riding the motorcycle with mischievous and then showing the bad attitude. Then factors that affect the subjective well being at the students who are broken home such as the condition of their family,the response or the lack of attention and the parents who are busy. Kata Kunci: adolescent, junior high school students, subejctive well-being, broken home